Integration of Living Law as an Optimization of Diversion in the Juvenile Justice System in Indonesia - Beniharmoni Harefa; Kayus K Lewoleba; Zico Junius Fernando (Universitas Negeri Semarang, 2026)
The implementation of diversion in the Juvenile Criminal Justice System in Indonesia still faces various obstacles that result in less than optimal implementation. These obstacles include limited human resources with specific competencies in the juvenile criminal justice system, weak coordination between law enforcement officials, limited supporting facilities and infrastructure, and low legal literacy among the public, which cumulatively create a gap between the normative objectives of the juvenile criminal justice system based on the principles of restorative justice and the best interests of the child and the actual conditions in the field. This study aims to comprehensively analyze the implementation of diversion, identify emerging obstacles, and formulate an ideal model for implementing diversion that aligns with the values of living law in society by comparing the living laws of the Balinese, Baduy, Dayak, and Nias communities. The method used combines a normative juridical approach, through a review of legislation, legal doctrine, and relevant literature, with empirical studies conducted through quantitative and qualitative data collection, case studies, interviews, and Focus Group Discussions (FGDs) with law enforcement officials, academics, and child protection practitioners. The results of the study indicate that the success rate of diversion in the last four years has tended to fluctuate, with an increase in the number of cases directed to diversion, but not always accompanied by an improvement in the quality of resolution. The identified barriers are structural, cultural, and technical, which interact with each other and influence the effectiveness of implementation. In addition, the potential for integrating customary legal values as a means of strengthening social legitimacy and increasing compliance with diversion agreements was discovered.